Страхові виплати в системі пенсійного забезпечення України - Дуркач, Лілія Василівна; Durkach, Liliia Vasylivna (Національний університет "Львівська політехніка", 2024)
Закон України "Про загальнообов’язкове державне пенсійне страхування" (2003) — базовий нормативний акт, що визначає принципи пенсійного страхування, умови призначення пенсій і порядок здійснення страхових виплат. Об’єкт дослідження: є система пенсійного забезпечення України. Предмет дослідження: є страхові виплати у рамках пенсійного забезпечення. Метою дослідження: дослідити на теоретичному та емпіричному рівнях особливості страхових виплат у пенсійній системі України. Результати дослідження: ефективність системи пенсійного забезпечення України значною мірою залежить від удосконалення механізму страхових виплат, а саме – їх своєчасності, достатності та прозорості; за умов належного реформування системи обов’язкового та добровільного пенсійного страхування можливе підвищення рівня соціального захисту пенсіонерів та забезпечення фінансової стабільності пенсійного фонду.

The Law of Ukraine "On Mandatory State Pension Insurance" (2003) is the fundamental legal act that defines the principles of pension insurance, the conditions for granting pensions, and the procedure for making insurance payments. Object of research: pension provision system in Ukraine. Subject of research: insurance payments within the framework of pension provision. The purpose of the study is to explore the features of insurance payments in Ukraine's pension system at both theoretical and empirical levels. Research results: the effectiveness of Ukraine's pension system largely depends on improving the mechanism of insurance payments, namely their timeliness, adequacy, and transparency. With proper reform of the mandatory and voluntary pension insurance systems, it is possible to enhance the level of social protection for pensioners and ensure the financial stability of the Pension Fund.
Insurance payments in the Ukrainian pension system
Keywords: 6.232.00.00; страхові виплати; соціальне страхування; пенсійне забезпечення; ПФУ; insurance benefits; mandatory social insurance system; pension provision system; Pension Fund of Ukraine (PFU) List of sources used: 1. Pension Fund of Ukraine. (n.d.). Structure and functions of the Pension Fund of Ukraine. Retrieved from https://www.pfu.gov.ua 2. IFES Ukraine. (n.d.). Digital solutions unlock pensions for a Ukrainian retiree displaced by war. Retrieved from https://www.ifesukraine.org 3. National Institute for Strategic Studies. (n.d.). The socio-demographic situation in Ukraine: Ways to overcome the consequences of war. Retrieved from https://niss.gov.ua/news/articles/sotsialno-demohrafichna-sytuatsiya-v-ukrainishlyakhy-podolannya-naslidkiv-viyny